Голови Ніжинського окружного суду у світлі матеріалів фонду 358 - Мінченко, М.В. (Сіверщина в історії України, 2022)
У статті реконструйовано життєвий і професійний шлях голів Ніжинського окружного суду на основі послужних списків, що зберігаються у фонді 358 Відділу забезпечення збереженості документів Державного архіву Чернігівської області (м. Ніжин). Методологія дослідження ґрунтується на принципах історизму, об’єктивності, аналізу, індукції, а також історико-генетичному, історико-порівняльному методах. The article reconstructs the life path and career way of Nizhyn District Court Heads on the basis of track records kept in the collection of materials 358 of the Department of Ensuring the Preservation of Documents of State Archives of Chernihiv Region (Nizhyn, Ukraine). The research methodology is based on the principles of historicism, objectivity, analysis, induction, as well as genetic and сomparative historical methods. It was found that they began their careers as junior assistant secretaries, candidates for the position of judges. Lawyers gained legal experience in the Department of Ministry of Justice and in court chambers. During their career for conscientious work they were awarded the orders: St. Stanislav of IIIrd, IInd, Ist degrees, St. Anna of IInd, Ist degrees, St. Vladimir of IVth, IIIrd degrees, and medals: «In memory of Emperor Oleksandr III», «In memory of the war of 1812». They were enlisted in the ranks of a real state adviser as the result of the successful career as the lawyer.